2015
DOI: 10.2147/coaya.s62236
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to promote regular exercise in adolescent and young adult cancer survivors

Abstract: Adolescents and young adults (AYAs) diagnosed with cancer are at increased risk for current and future health problems and premature death. Given the known risks for increased mortality and morbidity, fostering the development of exercise behaviors that may target the specific late effects experienced by AYA cancer survivors is crucial for healthy aging. Exercise is particularly important in the mitigation of late effects as it alters metabolic pathways that ultimately influence the development of chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Several reviews have confirmed the importance of developing strategies to promote physical activity and health behaviour changes in young cancer survivors. 1 , 2 The positive impact of vigorous physical activity on the risk for cardiovascular events was documented in reports from the Childhood Cancer Survivor Study. 3 5 Hodgkin’s lymphoma survivors who regularly underwent vigorous exercise of ⩾9 metabolic equivalent (MET)-hours per week had a significantly lower risk of treatment-related cardiovascular events than survivors who did not meet the physical activity guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have confirmed the importance of developing strategies to promote physical activity and health behaviour changes in young cancer survivors. 1 , 2 The positive impact of vigorous physical activity on the risk for cardiovascular events was documented in reports from the Childhood Cancer Survivor Study. 3 5 Hodgkin’s lymphoma survivors who regularly underwent vigorous exercise of ⩾9 metabolic equivalent (MET)-hours per week had a significantly lower risk of treatment-related cardiovascular events than survivors who did not meet the physical activity guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The higher physical activity is associated with better health-related quality of life across the domains of physical social and cognitive functioning in adolescents. 2 School-based nutrition education research studies were based primarily on a knowledge-attitude-behavior approach, while disease reduction/health enhancement studies were behaviorally oriented and generally based on social learning theory. Likewise, previous research nutrition and education are closely interlinked.…”
Section: Introductionmentioning
confidence: 99%